The awareness of blindness related to misuse of illicit liquor containing methanol: A community study - Indra Tri Mahayana; Tatang Talka Gani; Suhardjo Pawiroranu (Journal of Community Empowerment for Health, 2018)
Methanol is a cheap organic solvent and additive in the production of illicit liquors. There are many recorded incidences in Indonesia regarding methanol intoxication induced visual loss. We aimed to investigate the level of awareness of liquor-containing methanol misuse in the community related to its hazard of visual loss. Participants were recruited from 3 primary health care units which represent the population of rural communities in Yogyakarta, Indonesia and then divided into two groups: drinkers (cases) and nondrinkers (control). The participants answered closed questions in a questionnaire about knowledges related to the misuse of illicit liquor. Forty participants (mean age: 39.8 ± 13.39) completed the questionnaires. There were 40% and 60% of participants who reside in the city and suburbs; their education levels were 2.5%, 12.5%, 30%, 35%, and 7.5% for uneducated, elementary, junior, senior high school, and undergraduate, respectively. There were 6 drinker and 34 nondrinker participants (sex difference p <0.001). Only 1 drinker and 7 nondrinkers answered correctly regarding the ethanol based liquor. Fifty percent of drinkers and 32.35% of nondrinkers were aware that illicit liquors were most probably mixed with methanol. The drinkers were aware that liquor-containing methanol can cause sudden death (33.33%) or sudden visual loss (33.33%), while 55.8% nondrinker answered only sudden death. Participants’ awareness levels regarding the content and the visual outcome of methanol-containing liquor remain low. From this pilot study, we confirmed the need to conduct further research with a larger sample size, followed by clear ethical considerations for prevention.